Proust Anny Iwaszkiewiczowej - Cieliczko, Małgorzata (Zagadnienia Rodzajów Literackich, 2022)
The article concerns the reception of Marcel Proust’s novels by Anna Iwaszkiewiczowa (1897–1979) — an excellent expert in literature, music and painting, polyglot, erudite, humanist with a predilection for the exact sciences. She was the first translator of, In Search of Lost Time into Polish; the excerpts she translated testify not only to her outstanding talents at translation, but also to her reading insight and a kind of closeness to Proust’s writing and thought. Iwaszkiewiczowa also translated important critical articles by foreign authors to familiarize Polish readers with European proustological discussions. In addition, she devoted a lot of attention to the French author in her private journals, but above all, she creates her own, inspiring interpretations of Proust’s work in literary essays. The juxtaposition of the writings of Marcel Proust and Joseph Conrad turns out to be particularly interesting and fresh, though surprising at first. This article analyzes these texts, presenting them in the context of contemporary aesthetic, philosophical and even physical concepts (including Witkacy’s “pure form”, Rudolf Otto’s “numinosum”, Hermann Minkowski’s “space-time”), to which Iwaszkiewiczowa referred directly or indirectly. Parallel reading of both types of her considerations — those scattered in dailies, where she noted private impressions, as well as those announced in the form of carefully prepared articles — brings an interesting and unique image of Proust and of Iwaszkiewicz herself. The article is an attempt to give the floor to Anna Iwaszkiewicz, who is commonly perceived as the wife of a well-known writer. The author of the article argues that the figure and creative output of Anna Iwaszkiewiczowa are worth careful reading and research analysis, and above all, a reminder.